INVESTIGATIONS IN THE LEE-WICK ELECTRODYNAMICS - Accioly, Antonio Jose [UNESP]; Gaete, Patricio; Helayel-Neto, Jose; Scatena, Eslley [UNESP]; Turcati, Rodrigo (World Scientific Publ Co Pte Ltd, 2011)
We consider the Lee-Wick (LW) electrodynamics, i.e. the U(1) gauge theory where a (gauge-invariant) dimension-6 operator containing higher derivatives is added to the free Lagrangian of the U(1) sector. A quantum bound on the LW heavy particle mass is then estimated by computing the anomalous electron-magnetic moment in the context of the aforementioned model. This limit is not only within the allowed range estimated by LW, it is also of the same order as that considered in early investigations on the possible effects of the LW heavy particle in e(-)e(+) elastic scattering. A comparative study between the LW and the Coulomb potentials is also done.
Keywords: LW electrodynamics; anomalous electron magnetic moment in the context of the LW electrodynamics; quantum bound on the LW heavy particle mass; LW nonrelativistic potential